Dating of Long Bone Fracture Healing among Egyptian Pediatrics by Radiography (X-Ray) - Amal Salama Mahmoud1 , Amany Mohamed Fahmy1 , Alaa Mohamed Mahmoud1, Amani Abdelfattah Bayomi1 , Ahm (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Estimating the timing of skeletal injury accurately is of great importance in forensic cases and has a significant bearing on the judicial process (related to abused children). This work aimed to assess dating of long bone healing in fractures occurring to children aged from 1 to 18 years through using plain radiography (X-Ray) which can determine 6 features of fracture healing process that are especially important in alleged cases of child abuse. The most commonly affected ages were “1-6” years presenting 68%. Males were the majority of cases (56%). The illustrated data of each feature of healing (6 features of fracture healing) form a prototype timetable of fracture healing. These data suggest that fractures with soft-tissue swelling alone are acute fracture (< 1 week old). Fractures with periosteal reaction alone are likely to be recent fracture (between 8 days and 3 weeks old). Once Remodelling, bridging & hard callus fractures detected then old fracture is expected (more than 6 weeks old).